MODERNISM AND WESTERN LITERARY INFLUENCES IN CHAIRIL ANWAR AND SUTAN TAKDIR ALISYAHBANA - Purba, Nurhayati; Mandalahi, Esterlita; Siregar, Grace; Siagian, Novitasari (LANGUAGE : Jurnal Inovasi Pendidikan Bahasa dan Sastra, 2025)
ABSTRACT This article explores the extent to which Western literature, particularly from Britain and the United States, influenced the development of modern Indonesian literature in the 20th century. The study employs a literature review and intertextual reading approach, involving the examination of theories on modernism and cultural interaction, as well as an analysis of Indonesian literary works that show Western influences, especially those by Chairil Anwar and Sutan Takdir Alisyahbana. The analysis draws on Sarwoto’s framework to map the development of Indonesian literary discourse in the context of modernity, ideology, and cultural identity. The discussion focuses on the adoption of Western literary styles, themes, and narrative structures. Modernism in Indonesian literature is understood as the result of tensions between local traditions and global cultural currents that have developed since the colonial period. Chairil Anwar is known for his expressive and individualistic style, reflecting existentialist influences, while Sutan Takdir Alisyahbana emphasizes rationality and renewal, in line with the spirit of modern humanism. Both figures did not merely adopt Western influences passively but adapted them to the Indonesian socio-cultural context. As a result, a distinctive form of modern Indonesian literature emerged—one that bridges local cultural heritage with universal ideas. This study demonstrates that modern Indonesian literature is the product of dynamic interactions between internal and external forces and contributes to a deeper understanding of literature as a product of global cultural exchange. ABSTRAK Artikel ini membahas sejauh mana sastra Barat, khususnya dari Inggris dan Amerika, memengaruhi perkembangan sastra Indonesia modern pada abad ke-20. Penelitian ini menggunakan pendekatan studi pustaka dan pembacaan intertekstual, dengan tahapan yang mencakup penelaahan teori-teori modernisme dan interaksi budaya, serta analisis karya sastra Indonesia yang menunjukkan pengaruh Barat, terutama tulisan Chairil Anwar dan Sutan Takdir Alisyahbana. Analisis dilakukan dengan merujuk pada kerangka Sarwoto untuk memetakan perkembangan wacana sastra Indonesia dalam konteks modernitas, ideologi, dan identitas budaya. Pembahasan difokuskan pada gaya penulisan, tema, dan struktur naratif yang diadopsi dari tradisi sastra Barat. Modernisme dalam sastra Indonesia dipahami sebagai hasil dari ketegangan antara tradisi lokal dan arus budaya global yang berkembang sejak masa kolonial. Chairil Anwar dikenal karena gaya ekspresif dan individualistisnya yang mencerminkan semangat eksistensialisme, sedangkan Sutan Takdir Alisyahbana mengedepankan rasionalitas dan semangat pembaruan, sejalan dengan ide-ide humanisme modern. Keduanya tidak hanya menyerap pengaruh luar, tetapi juga menyesuaikannya dengan realitas sosial budaya Indonesia. Hasilnya adalah corak sastra modern Indonesia yang khas, yang menjembatani warisan budaya lokal dengan ide-ide universal. Studi ini menunjukkan bahwa sastra Indonesia modern lahir dari interaksi dinamis antara pengaruh internal dan eksternal, serta memberikan kontribusi penting dalam pemahaman sastra sebagai produk dari pertukaran budaya global.